KARDIOCHIRURGIA DOROSŁYCHTranscatheter aortic valve implantations in patients who are poor candidates for surgery – invasive cardiologists and cardiac surgeons will do it together - Wilczek, Krzysztof; Chodór, Piotr; Przybylski, Roman; Niklewski, Tomasz; Kusa, Jacek; Głowacki, Jan; Krasoń, Marcin; Nadziakiewicz, Paweł; Gąsior, Mariusz; Kalarus, Zbigniew; Poloński, Lech; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The authors present the state of knowledge concerning transcatheter aortic valve implantation technique in elderly patients with high risk of standard surgical aortic valve replacement. Indications and contraindications to this new treatment modality are discussed in detail. The technique introduced by A. Cribier in France nearly 7 years ago is still evolving and it seems to meet an increasing demand for such procedures. Both transfemoral and transapical approaches are described in more detail. The usefulness of the most important diagnostic imaging tools is discussed in preoperative and intraprocedural assessment of patients. The authors also provide important news that the first transcatheter aortic valves through the exposed heart apex have been successfully implanted in Poland.